The Ingenious Structure of Central Rotor Apparatus in V(o)V(1); Key for Both Complex Disassembly and Energy Coupling between V(1) and V(o) - Nakanishi, Atsuko (Public Library of Science, 2015)

(untitled) (PLoS One)
Vacuolar type rotary H(+)-ATPases (V(o)V(1)) couple ATP synthesis/hydrolysis by V(1) with proton translocation by V(o) via rotation of a central rotor apparatus composed of the V(1)-DF rotor shaft, a socket-like V(o)-C (eukaryotic V(o)-d) and the hydrophobic rotor ring. Reconstitution experiments using subcomplexes revealed a weak binding affinity of V(1)-DF to V(o)-C despite the fact that torque needs to be transmitted between V(1)-DF and V(o)-C for the tight energy coupling between V(1) and V(o). Mutation of a short helix at the tip of V(1)-DF caused intramolecular uncoupling of V(o)V(1), suggesting that proper fitting of the short helix of V(1)-D into the socket of V(o)-C is required for tight energy coupling between V(1) and V(o). To account for the apparently contradictory properties of the interaction between V(1)-DF and V(o)-C (weak binding affinity but strict requirement for torque transmission), we propose a model in which the relationship between V(1)-DF and V(o)-C corresponds to that between a slotted screwdriver and a head of slotted screw. This model is consistent with our previous result in which the central rotor apparatus is not the major factor for the association of V(1) with V(o) (Kishikawa and Yokoyama, J Biol Chem. 2012 24597-24603).